THE PROBLEM OF THE PRINCIPLE OF RECIPROCITI IN THE PROCESS OF RECOGNITION-ENFORCEMENT OF THE FOREIGN COURTS DECISIONS (Law and world, 2018)
In this work we discussed an important and troubling institution of international civil procedure law, known as the principle of “reciprocity” and its notion and faces. The reciprocity principle is particularly evident in the process of execution in judicial decisions of a foreign state in Georgia. In this regard, we discussed such issues as the institution’s approach to the state, its sovereignty and if Georgia strictly addresses the use of this principle, the possible problematic consequences of the use of this institution.